Transfer of Pilinia from Ectocarpales to Ishigeales (Phaeophyceae) with proposal of Piliniaceae fam. nov., and taxonomy of Porterinema in Ectocarpales. Issue 3 (3rd July 2022) - Kawai, Hiroshi; Hanyuda, Takeaki; Henry, Eric C.
ABSTRACT: Molecular phylogeny based on concatenated sequences of chloroplast atp B, psa A, psb A, psb C and rbc L genes indicates that the filamentous brown alga Pilinia rimosa is phylogenetically distant from the Ectocarpales, in which it has been classified (as Waerniella lucifuga ). In the tree, Pilinia was sister to the clade comprised of Ishige and Petroderma (Ishigeales) supported by high statistical values. Observations of unialgal P. rimosa cultures originating from Helgoland (Germany), England (UK), Woods Hole (USA) and Newfoundland (Canada) showed a direct type of life history with reproduction by characteristic unilocular zoidangia typically forming only four zoids. Despite the description of plurilocular zoidangia in Kuckuck's account as well as in later publications, we conclude that those observations were based on misinterpretation of the very small unilocular zoidangia formed in series, often with longitudinal walls between zoidangia. Pilinia rimosa grows in caves or crevices in rocks, and on walls or wood pilings in deep shade in the upper intertidal and spray zone, and is therefore regarded as a marine species, but it could also survive and mature in freshwater medium. We propose the establishment of a new family Piliniaceae for Pilinia and place it in Ishigeales. Molecular and morphological analysis of the culture strains, SAG 124.79 and SAG 2381, identified as the euryhaline alga Porterinema fluviatile, indicated that SAG 124.79 is in fact P. rimosa . However, SAG 2381 is true P. fluviatile, also displaying the characteristic plurilocular zoidangia. Porterinema was shown to be a member of the Chordariaceae, Ectocarpales sensu lato .